Makna Sakīnah Dalam Al-Qur’an: (Analisis Semiotika Roland Barthes Terhadap Q.S. Al-Rum (30): 21) - Jeri Saputra (Yayasan Syamil Quran Nunukan, 2024)
Peace and harmony are fundamental ideals in married life, representing important aspirations for every individual. The concept of a sakīnah family has been known since the era of the Prophet Muhammad, as evidenced by his exemplary interactions with his wives. The term sakīnah is explicitly mentioned in the Qur'an, specifically in QS. Ar-Rum (30): 21, highlighting the need to examine the linguistic structure of the verse to achieve a comprehensive understanding of its meaning. This study seeks to analyze the term sakīnah in QS. Ar-Rum (30): 21 through the lens of Roland Barthes' semiotic theory, contextualized within a contemporary framework. Using a literature-based descriptive-analytical methodology, this study focuses on the linguistic study of the term sakīnah and its semiotic implications as articulated by Barthes. The findings show that, linguistically, sakīnah signifies a state of tranquility achieved through certain actions. From a mythological point of view, sakīnah goes beyond the conjugal bond, encompassing a deep sense of tranquility that permeates the wider family structure. Therefore, the concept of sakīnah in QS. Ar-Rum (30): 21 offers a nuanced perspective on family harmony, demonstrating its enduring relevance to contemporary contexts while contributing new insights to Qur'ānic studies through the integration of semiotic theory.